Behavioral patterns of parasitoid phorids (Diptera: Phoridae) of Atta colombica (Hymenoptera: Formicidae) - Bedoya Cochet, Robin (2017)
In ecology, the success of parasitoid-host interactions is determined by the behavior of seeking, recognition, attack and defense deployed by the participants in the interaction. Our study aimed to understand the behavioral patterns between parasitoid phorids and their host Atta colombica from a forest fragment of Córdoba department, Colombia. We observed three nests of Atta colombica, from December 2013 to Januray 2015 (including dry and rainy seasons), for a total effort of 189 hours. We observed Phorids, their attacks to ants and collected their loads; we also considered differences in the way the parasitoids attacked and observed the microhabitat they preferred. A total of 52 individuals of Eibesfeldtphora attae and 54 of Apocephalus colombicus were collected. Apparently there was no preference for the size of the ants that were attacked by phorids, but larger loads were selected to land on them. When the ants responded to the phorid attack, they used individual defenses (adopting positions or increasing their speed) or grupal defenses (closer ants attacking the phorid). Parasitoid phorids have specialized their behavior, in order to ensure a successful attack on their host, who responded by modifying its behavior, according to the attacker (parasitoid).